Constitutionality Of Mechanism Approval Government Regulation Replacement Act In Law Number 12 Of 2011 Concerning The Formation Of Laws And Regulations - M Ilham Putuhena (NOMOI Law Review, 2020)
The issue of the mechanism for the approval of the laws and regulations needs to be assessed for their constitutionality because it will deal with the authority of the President and the House of Representatives (DPR) in the formation of legislation.The method used in this legal research is the normative juridical method.The results showed that the unconstitutionality of Article 52 and Article 71 of Law 12 of 2011 was because there was a reduction in the authority of the DPR in the Perpu made by the President because the DPR did not yet have the authority to refuse all or accept a portion of the Perpu with conditions for improvement.Keyword: Constitutional, Perpu, DPR, President.